2012
DOI: 10.1093/cercor/bhs154
|View full text |Cite
|
Sign up to set email alerts
|

Age-Based Comparison of Human Dendritic Spine Structure Using Complete Three-Dimensional Reconstructions

Abstract: Dendritic spines of pyramidal neurons are targets of most excitatory synapses in the cerebral cortex. Recent evidence suggests that the morphology of the dendritic spine could determine its synaptic strength and learning rules. However, unfortunately, there are scant data available regarding the detailed morphology of these structures for the human cerebral cortex. In the present study, we analyzed over 8900 individual dendritic spines that were completely 3D reconstructed along the length of apical and basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
180
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(200 citation statements)
references
References 45 publications
19
180
1
Order By: Relevance
“…Dendritic spines may represent a primary site of structural plasticity in the adult brain, and spine plasticity seems to play an important role in long-term memory in rodents (Sanders et al, 2012). Dendritic spine plasticity in the prefrontal cortex is reduced in aged rodents (Bloss et al, 2011), and spine density is likely reduced in aging (Jacobs et al, 1997, Esiri, 2007, Freeman et al, 2008, Benavides-Piccione et al, 2013) (see Figure 13). …”
Section: Neuroplasticity In the Aging Brain – A Critical Vulnerabimentioning
confidence: 99%
See 2 more Smart Citations
“…Dendritic spines may represent a primary site of structural plasticity in the adult brain, and spine plasticity seems to play an important role in long-term memory in rodents (Sanders et al, 2012). Dendritic spine plasticity in the prefrontal cortex is reduced in aged rodents (Bloss et al, 2011), and spine density is likely reduced in aging (Jacobs et al, 1997, Esiri, 2007, Freeman et al, 2008, Benavides-Piccione et al, 2013) (see Figure 13). …”
Section: Neuroplasticity In the Aging Brain – A Critical Vulnerabimentioning
confidence: 99%
“…Benavides-Piccione et al (2013) 3D reconstructed 8900 individual dendritic spines from layer III pyramidal neurons in the cingulate cortex from two male humans of age 40 and 85 years, using intracellular injections of Lucifer Yellow in fixed tissue. The left two panels show the 3D reconstruction of the complete morphology of each spine of an apical dendritic segment at 100 μm distance from the soma, and the estimation of the spine volumes shown in color codes (0–1.345 μm 3 ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Loss of dendritic spines in the synapses of the prefrontal cortex is correlated with cognitive decline and may precede AD as well, though this is still a matter of intense study and investigation. 22,23 Estrogen receptors are present in excitatory synapses in the prefrontal cortex, 24 and it has been shown that estradiol enhances cognitive performance in nonhuman primates through partial restoration of the thin spines. 24 Thus, estrogen receptors and related signaling pathways may provide therapeutic targets for cognitive decline.…”
Section: Cognitive Aging and Alzheimer's Diseasementioning
confidence: 99%
“…Changes in synapses and spines and cell body shrinking have been put forward as hypotheses to describe these phenomena (FJELL et al, 2015d). In the case of spines, a major decrease in spines has been observed, regardless of the distance to the neuron body, in the comparison of the cingulate cortex of a middle-aged and an older adult (BENAVIDES-PICCIONE et al, 2013). Increases in glia and small-body neurons and decreases in large cell-body neurons populations are also observed throughout aging, contributing to a near constant cell density (MARTÍNEZ-PINILLA et al, 2016;TERRY;DETERESA;HANSEN, 1987).…”
Section: Scientific Findings From Neuroimagingmentioning
confidence: 99%